Prevalence and Psychological Consequences of Cyberbullying among Students of Medical Departments at the Technical Medical Institute in Mosul, Iraq: A Cross-Sectional Study - Mohamed Sadeq Younes Alibrahim; Ehab Mohammed shaker; Salim Shihab Almetewty (Indonesian Journal of Nursing and Health Care, 2026)
Background: Cyberbullying, defined as the digital platforms used for upsetting or intimidating others, is an increasingly widespread issue amongst university students, especially those in healthcare students. This phenomenon has adversely impact victims' psychological health, public relationships, and educational performance.Objective: The current study intended to assess the prevalence, appearances, and psychological impression of cyberbullying that may affect medical departments students at the Technical Medical Institute in Mosul.Methods: The researchers guided a cross-sectional study at the Technical Medical Institute in Mosul, via convenience sampling, handling 200 students in customary areas like the library and the student lounge. This numbers was drawn from a total student population of 1,775, based on 2023 enrollment numbers⁴. The researchers requested from each participants to complete a validated Cyberbullying Questionnaire, which measured four key areas: verbal threats, social exclusion, obscene/sexual content, and psychological impact.Results: The study implied 200 medical departments students per an average age of 22.5 ± 4.2 years, 61% of them was female, verbal terror and social exclusion being the most cyberbullying forms of the sample. The Psychological impacts, including anxiety and decreased academic accomplishment, were reported, chiefly among females and students in Nursing and Community Health departments.Conclusion: Cyberbullying corresponds to a widespread concern within medical education environments, beside profound psychological consequences. The findings highlight the necessity for directed interventions, including understanding struggles, advising services, and partner support programs, to address this expanding challenge.